Analysis of Critical Thinking Ability in Physics of High School Students - Aqil Marwan; Khaeruddin Khaeruddin; Ahmad Dahlan; Arief Aulia Rahman (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study describes students’ critical thinking skills in static fluid learning across five public senior high schools in the West Bone region under different learning models. A quantitative descriptive survey was conducted involving 153 grade XI science students selected through purposive sampling from a population of 524 students. The research instrument consisted of 13 essay items developed from five critical thinking indicators and validated through expert review and reliability testing. Data were analyzed using descriptive statistics and category conversion. The findings show that students’ critical thinking skills were generally in the good category, with the highest mean score found in the Problem-Based Learning group (29.63), followed by Project-Based Learning (27.47), Discovery Learning (26.11), Inquiry Learning (24.60), and Cooperative Learning (22.74). The results indicate that learning models emphasizing problem solving and authentic tasks tend to support higher critical thinking performance. These findings suggest the importance of selecting contextual, student-centered learning models to strengthen critical thinking in physics education.